The effect of thyroid autoantibody positivity on the functions of internal ear - AKIN TELLİ, TUĞBA (SPRINGER, 2017)
The objective of the study is to investigate if any significant difference exists in hearing thresholds and tympanometric examination results among patients whose thyroid antibody positivity was detected approximately 1 year or at least 5 years ago. Study population aged less than 40 years consisted of 17 patients who had thyroid antibody positivities for an average of 1 year (first group), 15 patients who were followed up for at least 5 years for thyroid antibody positivity (second group), and 18 volunteers (third group). Tympanometric examination results, stapes reflex, SRT, SD, and pure tone values were examined. When the second group and the third group were compared, significant results were obtained at hearing frequencies between 500 and 4000 Hz. When the first group and the third group were compared, only at 1000 Hz threshold significant results were obtained. During evaluation of hearing frequencies between 250 and 8000 Hz, significant results were not observed between the second group and the first group. When the first and the second groups were compared with the control group, significant results were obtained as for tympanometric examination findings and significant results were not observed between the second group and the first group. A significant difference was not detected as for the results of stapes reflex. Since thyroid antibody positivity affects the functions of internal ear, these patients should be more closely monitored. Since these effects become deeper in line with increased exposure to autoantibody positivity, variations in auditory responses should be more attentively monitored.
Keywords: Hashimoto's thyroiditis; Thyroiditis; Autoantibody; Autoimmune hearing loss; SENSORINEURAL HEARING-LOSS; EUTHYROID HASHIMOTOS-THYROIDITIS; AUDIOLOGICAL FINDINGS; ACOUSTIC REFLEX; INNER-EAR; HYPERTENSION; DYSFUNCTION; DISORDERS; DISEASE; RISK